A comparison between Monte Carlo simulation and finite-volume scheme for reliability assessment of multi-state physics systems. (June 2018) - Lin, Yan-Hui; Li, Yan-Fu; Zio, Enrico
Highlights: Dependencies among degradation processes in MSPS are modeled by PDMP. A comparative study of MC simulation and FV scheme for reliability assessment of MSPS is conducted. Two case studies regarding a real industrial system are considered. Guidelines for the selection of the two approaches are provided. Abstract: Multi-state physics systems (MSPS) modeling framework incorporates multi-state models that describes the systems degradation/maintenance process through transitions among discrete states, and physics-based models that describe the degradation process within the states by using physics knowledge and equations. In previous works, piecewise-deterministic Markov process (PDMP) has been adopted to treat the system dynamics and the degradation dependence in MSPS. For reliability assessment, Monte Carlo simulation and finite-volume method are two widely used numerical approaches to solve PDMP. In the present work, a comparative study considering different evaluation criteria of the two approaches is conducted on two representative case studies. We provide clear guidelines for the selection of the two approaches.